BASICS OF ORGANIZATION OF INCOME ACCOUNT OF COMMERCIAL BANKS - Qodirov Javohir Qaxramon o‘g‘li (Scholars Digest Publishing, 2024)
The article describes the structure of income and organization of the accounts of commercial banks in our country. The article describes the structure of income of commercial banks today based on modern banking features.
Keywords: commercial banks, payment services, income, accounting, modern services.